Muḥammad is not the father of any of your men: the making of the last prophet - Powers, David Stephan (Divinations: Rereading late ancient religion, 2009)
Pt. I. Fathers and sons -- The foundation narratives of Judaism, Christianity, and Islam -- Adoption in the Near East: from antiquity to the rise of Islam -- The abolition of adoption in early Islam -- Pt. II. From sacred legend to sacred history -- The repudiation of the beloved of the messenger of God -- The battle of Mu'ta -- The martyrdom of the beloved of the messenger of God -- Pretexts and intertexts -- Pt. III. Text and interpretation -- Paleography and codicology: Bibliothèque Nationale de France 328a -- Kalāla in early Islamic tradition -- Conclusion